The Effect of Crossword Puzzle on Developing Students’ Vocabulary at Seven Grade of SMP Pangeran Antasari Medan - Nurmahyuni Asrul; Azizah Husda; Dwi Suci Amaniarsih (Randwick International of Education and Linguistics Science Journal, 2022)
The researchers’ aim for this research was to determine the significance of using crossword puzzles in developing students' vocabulary at Pangeran Antasari Medan's seventh grade. The quantitative design was used in this study. This study's population consisted of 50 students. Furthermore, the researchers used 50 students as a sample and divided them into two different groups, experimental and control groups. The study's instrument was a fill-in-the-blanks (Pre-test and Post-test) or crossword puzzle. Based on the clarification over, the author analyzed the score utilizing the T-test equation, and the result was T-observed was 2.92 and t-table was 1,684, indicating that T-observed was more prominent than T-table. At the critical level, p= 0.05 and df= nx=ny-2 = 48. This implies that Crossword Puzzle Strategy features a noteworthy affect on students' learning.